2015
DOI: 10.1111/and.12442
|View full text |Cite
|
Sign up to set email alerts
|

Effect of androgen deprivation on the expression of aquaporins in rat prostate and seminal vesicles

Abstract: The aim of this study was to investigate the level of secretions of prostate and seminal vesicles and its association with the expression of AQP0, 1, 4, 5, 6 and 8 in castrated rats. Eight-week-old male Sprague-Dawley (SD) rats (n = 18) were randomly divided into control group, castrated rats group and castrated followed testosterone replacement group. Four weeks after surgery, the secretions and expression of AQP0, 1, 4, 5, 6 and 8 of prostate and seminal vesicles were determined. Serum testosterone was signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…AQP1 is expressed in seminal vesicle in rats ; it is responsible for bidirectional water transport through membranes . It has been demonstrated that TP treatment of ORX rats influences AQP1 expression . In agreement to data demonstrating a downregulation of uterine AQP1 after estradiol treatment of ovariectomized rats , our data show a downregulation of AQP1 by TP (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…AQP1 is expressed in seminal vesicle in rats ; it is responsible for bidirectional water transport through membranes . It has been demonstrated that TP treatment of ORX rats influences AQP1 expression . In agreement to data demonstrating a downregulation of uterine AQP1 after estradiol treatment of ovariectomized rats , our data show a downregulation of AQP1 by TP (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…For seminal fluid preparation, the whole fresh seminal vesicle was punctured using a micropipette tip and transferred into an Eppendorf tube. The level of seminal fluid was represented as the weight of seminal fluid/ the fresh seminal weight × 100 as previously described (Tian et al, ). PBS was then added to the seminal fluid, and it was sonicated using an ultrasonic homogeniser on ice.…”
Section: Methodsmentioning
confidence: 99%
“…Rats in the replacement groups (A and D) were subcutaneously injected with testosterone propionate (3 mg/kg every other day) after castration. Rats in the other groups (B, C, E and F) were injected with equal amounts of vegetable oil (Tian, Xia, Jiang, He, & Lin, ).…”
Section: Methodsmentioning
confidence: 99%